Gambaran Kejadian Berpotensi Medication Errors Fase Prescribing Resep Pasien Rawat Jalan RSUD Arifin Achmad Riau: Description Event Potentially Medication Errors Phase Prescribing Outpatient Prescription Regional General Hospital Arifin Achmad Riau - Wardatul Jannah; Septi Muharni (LPPM Universitas Abdurrab, 2023)
This study aims to look at the percentage of occurrence of potentially overview phase prescribing medication errors in the outpatient prescription Regional General Hospital Arifin Achmad Riau province. This study is an observational study / survey descriptive. Sampling was done by accidental sampling method, the sample obtained in this study as many as 300 sheets of prescription outpatient entrance at the time of the research conducted at Arifin Achmad. The results showed that the highest percentage of incidence of medication errors that could potentially prescribing phase of outpatient prescription Arifin Achmadbased on the payment status is the highest percentage in the general patient prescription that is equal to 27.78%. Based on the origin prescribers percentage gained is a general practitioner in the amount of 26.32%. Based on the number of prescription drugs in the percentage of the highest incidence â‰¥5 is the amount of drug that is equal to 29.44%. Based on the patient's weight recipe completeness 96.67%, height pasien96,67% and this study was not found prescription that can not be read, and there is no drug name abbreviation unusual. These results indicate that the phase of prescribing medication errors in the outpatient prescription Arifin Achmad still high.